Racialising Religion in the Debate on Religious Freedom in Malaysia - Saskia Louise Shafer (Al-Jami'ah Research Centre, 2009)
This article summarises the results of a media analysis conducted by the example of one of the country’s biggest daily newspapers, the New Straits Times. With regard to the controversial religious freedom debate, it summarises what actors are involved in the discussion and how their positions are presented in the mainstream media. Several examples from articles show what strategies are employed in the discourse, such as the rhetoric of fear and crisis and the constant emphasis of racial and other supposedly separating categories. The close linkage of the categories ‘ethnicity’ and ‘religion’, which is manifested legally as well as politically, is perpetuated linguistically. Especially important in this context is the construction of a Muslim-Malay identity.